A framework for turnaround practitioners to assess reasonable prospect for ventures operating in the zone of insolvency - M. Pretorius (South African Journal of Business Management, 2017)
Turnaround practitioners (TPs) and business rescue practitioners (BRPs) are tasked with making the critical decision of whether a distressed business has reasonable prospect (RP) for reorganisation. Creditors often require the same determination because only businesses assessed to have a reasonable prospect can enter the rescue or reorganisation process. These determinations are difficult because they are made within a `zone of insolvency' (ZoI). Going concerns operate on a solvent basis but may slide into the ZoI where conditions are ambiguous, unclear and uncertain. At the same, time, the specific conditions and contexts of distressed businesses vary widely despite some generic similarities that may exist. Therefore, the decision about reasonable prospect depends largely on how TP and BRPs perceive and make sense of the ambiguous conditions within the zone of insolvency. Finally, creditors and courts rarely agree with such RP determinations, but no generic tool exists to satisfy all stakeholders. Hence, the decision of whether (or not) a distressed business has a reasonable prospect to embark upon a reorganisation intervention involves both rational and subjective assessment to make sense of the conditions present in the ZoI. An affordance framework with guiding scores is proposed to determine reasonable prospect.
Keywords: 650